2010
DOI: 10.1371/journal.pgen.1000858
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 Targets Srs2 to Complete Synthesis-Dependent Strand Annealing and to Promote Recombinational Repair

Abstract: Cdk1 kinase phosphorylates budding yeast Srs2, a member of UvrD protein family, displays both DNA translocation and DNA unwinding activities in vitro. Srs2 prevents homologous recombination by dismantling Rad51 filaments and is also required for double-strand break (DSB) repair. Here we examine the biological significance of Cdk1-dependent phosphorylation of Srs2, using mutants that constitutively express the phosphorylated or unphosphorylated protein isoforms. We found that Cdk1 targets Srs2 to repair DSB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
103
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 53 publications
(93 reference statements)
21
103
0
Order By: Relevance
“…Such genetic data are consistent with the ability of Srs2 to disassemble the Rad51 nucleoprotein filaments formed on single-stranded DNA (ssDNA) in vitro (20,40). In addition to directly inhibiting homologous recombination (HR), Srs2 is also involved in regulating HR outcomes to not produce crossover recombinants in the mitotic cell cycle (18,34,35).…”
supporting
confidence: 66%
“…Such genetic data are consistent with the ability of Srs2 to disassemble the Rad51 nucleoprotein filaments formed on single-stranded DNA (ssDNA) in vitro (20,40). In addition to directly inhibiting homologous recombination (HR), Srs2 is also involved in regulating HR outcomes to not produce crossover recombinants in the mitotic cell cycle (18,34,35).…”
supporting
confidence: 66%
“…7D). STUbLs are known to mediate proteasome degradation of SUMOylated substrates (Sriramachandran and Dohmen 2014), and Srs2 is itself SUMOylated (Saponaro et al 2010). Importantly, here we identified that Esc2 functions upstream of Slx5-Slx8-mediated action as a crucial regulator of Srs2 turnover (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…The SUMO targeted ubiquitin ligase (STUbL) Slx5-Slx8 complex plays a role in genome stability by controlling the turnover of SUMOylated factors in response to DNA damage (Sriramachandran and Dohmen 2014). As Esc2 and its Schizosaccharomyces pombe ortholog, Rad60, genetically and physically interact with Slx5-Slx8 (Prudden et al 2007;Sollier et al 2009) and as Srs2 is SUMOylated (Saponaro et al 2010;Kolesar et al 2012), we examined whether Srs2 degradation is also mediated by Slx5-Slx8. We found that Srs2 protein levels were stabilized following genotoxic stress in the absence of Slx5, similar to what we observed in esc2Δ (Fig.…”
Section: Local Regulation Of Recombination Genes and Development 2075mentioning
confidence: 99%
“…This explains the srs2 Δ puzzling phenotype which includes both recombination deficiency and hyper‐recombination. The anti‐recombination role of Srs2 is particularly important for inhibition of recombination at replication forks and involves complex regulation of Srs2 through post‐translational modifications at its C‐terminus (Saponaro et al , 2010; Kolesar et al , 2012). The C‐terminal part is not needed for the role of Srs2 in re‐synthesis of resected DNA, and therefore, the Srs2 pro‐recombination function is genetically separable from its role at replication forks.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Srs2 results in a paradoxical phenotype. On one hand, srs2 mutants are hyper‐recombinogenic (Aguilera & Klein, 1988), and on the other hand, they are deficient in DSB repair via HR and SSA (Vaze et al , 2002; Saponaro et al , 2010). Here we elucidate at the molecular level the role of Srs2 in multiple repair mechanisms involving extended DNA resection by showing that Srs2 is capable of dislodging Rad51 from ssDNA in order to promote loading of proliferating cell nuclear antigen (PCNA) and DNA replication machinery to restore dsDNA at repair loci.…”
Section: Introductionmentioning
confidence: 99%